Dual renormalization group flows in 4D - Abel, Steven; Bajc, Borut; Sannino, Francesco (Physical Review D, 2019)
We present a prescription for using the a central charge to determine the flow of a strongly coupled supersymmetric theory from its weakly coupled dual. The approach is based on the equivalence of the scale-dependent a parameter derived from the four-dilaton amplitude with the a parameter determined from the Lagrange multiplier method with scale-dependent R charges. We explicitly demonstrate this equivalence for massive free N=1 superfields and for weakly coupled SQCD.
EPrint Processing Status: Full text deposited in DRO